Protocol for differentiating murine 3T3-L1 and SVF-derived preadipocytes and isolating crude mitochondrial fractions - Churaibhon Wisessaowapak; Jeongmin Lee; Hyeonhui Kim; Seunghwan Son; Xue Feng; Lina Chang; Annie Hoang; Hetty Chen; Sarah Bedsted; Alan R. Saltiel (STAR Protocols)
Summary: Here, we present a protocol for differentiating 3T3-L1 preadipocytes and stromal vascular fraction (SVF)-derived preadipocytes from mice into mature adipocytes, followed by the isolation of crude mitochondrial fractions. This cost-effective and reproducible protocol is optimized for small-plate formats, compatible with standard reagents, and suitable for metabolic studies such as insulin resistance and mitochondrial function. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.